Two Coupled Forced‐Convection Boundary Layers of Counter‐Flow. Issue 7 (17th October 2016) - El‐sayed Mosaad, Mohamed
Abstract: In this study, the conjugate heat transfer problem of two forced‐convection boundary layers of counter‐laminar flow on plate sides is analyzed by employing the integral method. The analysis is conducted in a dimensionless way to generalize the solution. The dimensionless parameters governing the thermal coupling between the two convection layers are revealed from the analysis. These parameters give a measure of the relative importance of interactive heat transfer modes. Mean Nusselt number results are obtained for a wide range of the governing parameters.